Having a Calling on Board: Effects of Calling on Job Satisfaction and Job Performance Among South Korean Newcomers - Park, Jiyoung; Kim, Sinae; Lim, Myoungki; Sohn, Young Woo (Frontiers in Psychology, 2019)
Despite increasing research on calling, how calling functions for those experiencing transition from school to work and how their calling prior to working relates to later well-being and job outcomes has been understudied. The current study explored effects of perceiving a calling on job satisfaction and job performance, as measured at organizational entry and two years after organizational entry. Using a time-lagged collection of a sample of South Korean newcomers, the results based on structural equation modeling revealed that perceiving a calling was positively related to supervisor-rated job performance. Job involvement, which was measured one year later, fully mediated the relation between perceiving a calling and job satisfaction, but the hypothesized mediating role of job involvement on the link between perceiving a calling and job performance was not supported. We also examined moderating roles of perceived organizational support and perceived person-job fit on the relation between perceiving a calling on job involvement and found that perceived organizational support facilitated the effects of perceiving a calling on job involvement. Implications of these findings are discussed.